If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2m(1 + 4m) * 5 = -13 Reorder the terms for easier multiplication: -2 * 5m(1 + 4m) = -13 Multiply -2 * 5 -10m(1 + 4m) = -13 (1 * -10m + 4m * -10m) = -13 (-10m + -40m2) = -13 Solving -10m + -40m2 = -13 Solving for variable 'm'. Reorder the terms: 13 + -10m + -40m2 = -13 + 13 Combine like terms: -13 + 13 = 0 13 + -10m + -40m2 = 0 Begin completing the square. Divide all terms by -40 the coefficient of the squared term: Divide each side by '-40'. -0.325 + 0.25m + m2 = 0.0 Move the constant term to the right: Add '0.325' to each side of the equation. -0.325 + 0.25m + 0.325 + m2 = 0.0 + 0.325 Reorder the terms: -0.325 + 0.325 + 0.25m + m2 = 0.0 + 0.325 Combine like terms: -0.325 + 0.325 = 0.000 0.000 + 0.25m + m2 = 0.0 + 0.325 0.25m + m2 = 0.0 + 0.325 Combine like terms: 0.0 + 0.325 = 0.325 0.25m + m2 = 0.325 The m term is 0.25m. Take half its coefficient (0.125). Square it (0.015625) and add it to both sides. Add '0.015625' to each side of the equation. 0.25m + 0.015625 + m2 = 0.325 + 0.015625 Reorder the terms: 0.015625 + 0.25m + m2 = 0.325 + 0.015625 Combine like terms: 0.325 + 0.015625 = 0.340625 0.015625 + 0.25m + m2 = 0.340625 Factor a perfect square on the left side: (m + 0.125)(m + 0.125) = 0.340625 Calculate the square root of the right side: 0.583630876 Break this problem into two subproblems by setting (m + 0.125) equal to 0.583630876 and -0.583630876.Subproblem 1
m + 0.125 = 0.583630876 Simplifying m + 0.125 = 0.583630876 Reorder the terms: 0.125 + m = 0.583630876 Solving 0.125 + m = 0.583630876 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-0.125' to each side of the equation. 0.125 + -0.125 + m = 0.583630876 + -0.125 Combine like terms: 0.125 + -0.125 = 0.000 0.000 + m = 0.583630876 + -0.125 m = 0.583630876 + -0.125 Combine like terms: 0.583630876 + -0.125 = 0.458630876 m = 0.458630876 Simplifying m = 0.458630876Subproblem 2
m + 0.125 = -0.583630876 Simplifying m + 0.125 = -0.583630876 Reorder the terms: 0.125 + m = -0.583630876 Solving 0.125 + m = -0.583630876 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-0.125' to each side of the equation. 0.125 + -0.125 + m = -0.583630876 + -0.125 Combine like terms: 0.125 + -0.125 = 0.000 0.000 + m = -0.583630876 + -0.125 m = -0.583630876 + -0.125 Combine like terms: -0.583630876 + -0.125 = -0.708630876 m = -0.708630876 Simplifying m = -0.708630876Solution
The solution to the problem is based on the solutions from the subproblems. m = {0.458630876, -0.708630876}
| 2(2l-3+l)=36 | | -(3/x)=0 | | 13/6-1/2 | | 10+4+3x=7*3.5 | | 24.5=2.5-4c | | 7+7y=12x-56 | | -(3/x)0 | | 7v^2+224=-84v | | 10x+20y=360 | | a(n-5)+6=bn | | 6q+1+(q+11)= | | 16+3x=7*3.5 | | 30-45=18 | | 1.25m*7=43.25 | | 2x^2dy=(3xy-y^2)dx | | X+1.5x+0.5x=75 | | sqrt(3x^2+4)-2x=0 | | 4-15=-7 | | -4+3x=20x+9 | | X+1.5x+0.5x= | | l+2l-1+2l+1=30 | | log(x)+log(x-5)=log(5x) | | -4(j+2)=5(j-3) | | c+(3c)+(2.5c)=60 | | (7-x)(x^2+20)= | | (x-3)=50 | | 8+2.50x=30 | | 6x+6=-8+2x+22 | | 0.23(10000)-0.04y=0.06(y+10000) | | 12-4m=36-12m | | x^3-200x^2+2x=0 | | 8k+5=2k-15 |